Salivary Cortisol Levels and Periodontal Condition of Chemical Dependent Patients - Batista, Julia Arruda; Chiba, Fernando Yamamoto; Borges, Sabrina de Melo; Saliba, Tânia Adas; Garbin, Cléa Adas Saliba (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Background: Drug addiction can harm oral health, as the use of illicit substances can reduce salivary flow and the buffering capacity of saliva, facilitating the development of periodontal disease. Salivary cortisol levels can influence oral health, as increased levels of this hormone may be related to a decreased immune response, affecting periodontal tissues. Objective: To evaluate salivary cortisol levels and their relationship with the periodontal condition of chemical dependent patients. Methods: The study was carried out on 60 institutionalized chemical dependent patients. Data on sociodemographic characteristics were collected through interviews and periodontal condition was assessed using the Community Periodontal Index. Analysis of salivary cortisol levels was performed using the ELISA method. Results: Of the 360 mouth sextants, 59 (16.39%) were healthy; 69 (19.17%) had bleeding on probing; 75 (20.83%) had dental calculus; 79 (21.94%) had periodontal pockets; and 78 (21.67%) were excluded. The average number of healthy sextants was 0.98+1.83; of sextants with bleeding on probing was 1.15+1.64; of sextants with dental calculus was 1.25+1.78; of sextants with periodontal pocket was 1.32+1.71; and of excluded sextants it was 1.28+1.91. The concentration of salivary cortisol was significantly higher (p=0.0015) in patients who had at least one sextant with gingival bleeding (89.31+96.06) compared to those who did not have gingival bleeding (23.96+29.09). Conclusion: The patients presented severe damage to their periodontal condition and those with gingival bleeding had a higher concentration of salivary cortisol.